IMPROVEMENT OF METHODS FOR THE RESTORATION OF DEGRADED PASTURES BASED ON LAND MANAGEMENT PROJECTS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores modern approaches to the restoration of degraded pastures through the use of land management projects. Special attention is given to methods of rational land use and the implementation of comprehensive measures aimed at increasing pasture productivity. The causes of land degradation are analyzed, and scientifically grounded methods for their restoration are proposed, taking into account the natural and climatic conditions of the region. Practical examples from land management in the Kashkadarya region are provided, where successful methods for improving pasture conditions have been implemented.